Attitude of Hausa ESL Secondary School Students Towards Spelling and Writing in English - Muhammad Mukhtar Aliyu; Gambo A. Danladi (Universitas Jambi, Magister Program of English Education Department, 2018)
Writing skill is described as an essential language tool for students. Studies have shown that Hausa ESL secondary school students commit various errors in their writing in English. Various factors have been identified as responsible for the problems. However, the students’ attitude towards spelling and writing has not been investigated. It is believed that students’ attitude plays an important role in motivating and influencing their second-language learning. Therefore, the aim of this study is to explore the attitude and perception of Hausa ESL secondary school students towards English spelling and writing. The study adopts a survey research design where an intact class of 75 students from a secondary school in north-eastern Nigeria was selected. To collect the data for the study, a questionnaire was employed. The questionnaire comprises two sections: (i) attitudes toward English spelling and (ii) attitudes toward writing in English which include four writing purposes: (a) School Use, (b) Social Use, (c) Official Use, and (d) Creativity. Findings of the study revealed that the participants have a moderate positive attitude and perception towards English spelling and writing. The findings also indicated that the students’ attitude toward the School Use of English is the highest, whereas their Creativity in writing has the lowest means among the four purposes. In addition, the study revealed that there is a significant positive relationship between the participants’ attitude towards spelling and writing. To enhance students’ creative writing and thinking skills, the study suggests that literature in English should be made compulsory to all secondary school students. Story-reading and creative writing should be incorporated into the curriculum. Other extracurricular activities such as spelling completion should be organised to help the students.